Neurobiological features and response to eye movement desensitization and reprocessing treatment of posttraumatic stress disorder in patients with breast cancer. Issue 1 (1st January 2019) - Carletto, Sara; Porcaro, Camillo; Settanta, Carmen; Vizzari, Vincenzo; Stanizzo, Maria Rosa; Oliva, Francesco; Torta, Riccardo; Fernandez, Isabel; Moja, Mario Coletti; Pagani, Marco; Ostacoli, Luca
ABSTRACT: Background : Breast cancer (BC) is one of the most common invasive types of cancer among women, with important consequences on both physical and psychological functioning. Patients with BC have a great risk of developing posttraumatic stress disorder (PTSD), but few studies have evaluated the efficacy of psychological interventions to treat it. Furthermore, no neuroimaging studies have evaluated the neurobiological effects of psychotherapeutic treatment for BC-related PTSD. Objective : The study aimed to evaluate the efficacy of Eye Movement Desensitization and Reprocessing therapy (EMDR) as compared to Treatment as Usual (TAU) in BC patients with PTSD, identifying by electroencephalography (EEG) the neurophysiological changes underlying treatments effect and their correlation with clinical symptoms. Method : Thirty patients with BC and PTSD diagnosis were included, receiving either EMDR ( n =  15) or TAU ( n =  15). Patients were assessed before and after treatments with clinical questionnaires and EEG. The proportion of patients who no longer meet criteria for PTSD after the intervention and changes in clinical scores, both between and within groups, were evaluated. Two-sample permutation t -tests among EEG channels were performed to investigate differences in power spectral density between groups. Pearson correlation analysis was carried out between power bands and clinical scores. Results : At post-treatment, all patients treated with EMDR no longer met criteria for PTSD, while all patients treated with TAU maintained the diagnosis. A significant decrease in depressive symptoms was found only in the EMDR group, while anxiety remained stable in all patients. EEG results corroborated these findings, showing significant differences in delta and theta bands in left angular and right fusiform gyri only in the EMDR group. Conclusions : It is essential to detect PTSD symptoms in patients with BC, in order to offer proper interventions. The efficacy of EMDR therapy in reducing cancer-related PTSD is supported by both clinical and neurobiological findings.